Ratings-based regulation and systematic risk incentives - Iannotta, Giuliano (2022)
Funding agency and sponsor: CAREFIN, University of Tennessee, University of Virginia and Institut Européen d'Administration des Affaires. Funding text: An earlier version of this paper was titled “Bank regulation, credit ratings, and systematic risk.” Valuable comments were provided by the Editor Itay Goldstein, three anonymous referees, Tobias Berg, Thomas Cooley, Timotej Homar, Christine Parlour, Andrea Resti, Francesco Saita, Andrea Sironi, René Stulz, and Andrew Winton; participants of the 2011 International Risk Management Conference, the 2011 Bank of Finland Future of Risk Management Conference, the 2012 Financial Risks International Forum, the 2012 Red Rock Conference, the 2012 FDIC Bank Research Conference, the 2012 Banque centrale du Luxembourg Conference, the 2013 Financial Intermediation Research Society Meetings, the 2013 Banco de Portugal Financial Intermediation Conference, and the 2014 Wharton Liquidity and Financial Crises Conference; and seminar participants at Copenhagen Business School, the Federal Reserve Banks of Cleveland and San Francisco, the Federal Reserve Board, HEC Paris, Imperial College, Indiana University, INSEAD, the Korea Deposit Insurance Corporation, Universitá Bocconi, Universitat Pompeu Fabra, the University of Tennessee, the University of Virginia, and Warwick Business School. We are very grateful to CAREFIN for providing financial assistance. The views stated herein are those of the authors and are not necessarily those of the Federal Reserve Bank of New York or the Federal Reserve System